Targeting JUN, CEBPB, and HDAC3: A Novel Strategy to Overcome Drug Resistance in Hypoxic Glioblastoma - Gao, Yixing; Liu, Bao; Feng, Lan; Sun, Binda; He, Shu; Yang, Yidong; Wu, Gang; E, Guoji; Liu, Chang; Gao, Yuqi; Zhang, Erlong; Zhu, Bo (Frontiers in Oncology, 2019)
Hypoxia is a predominant feature in glioblastoma (GBM) and contributes greatly to its drug resistance. However, the molecular mechanisms which are responsible for the development of the resistant phenotype of GBM under hypoxic conditions remain unclear. To analyze the key pathways promoting therapy resistance in hypoxic GBM, we utilized the U87-MG cell line as a human GBM cell model and the human brain HEB cell line as a non-neoplastic brain cell model. These cell lines were cultured in the presence of 21%, 5% and 1% O2 for 24 h. We detected the changes in transcriptional profiling and analyzed the biological processes and functional interactions for the genes with different expression levels under different hypoxia conditions. The results indicated that those alterations of U87-MG cells presented specific transcriptional signature in response to diverse hypoxia levels. Gene ontology analysis revealed that the genes related to the DNA replication and cell cycle were suppressed, while the genes involved in tissue and system development to promote cancer development were activated following hypoxia. Moreover, functional interaction analysis suggested that the epigenetic regulator HDAC3 and the transcriptional factors CEBPB and JUN played a central role in organ and system developmental process pathway. Previous studies reported the global alterations caused by activation of HDAC3, CEBPB and JUN could form the molecular basis of the resistance to chemotherapy and radiation therapy of hypoxic GBM. In our study, the significant growth inhibitory effect of temozolomide on hypoxic GBM cells could be promoted under downregulation of these genes. The experiment suggested that HDAC3, CEBPB and JUN were closely involved in the drug-resistance phenotype of hypoxic GBM. In summary, we profiled the hypoxia-dependent changes in the transcriptome of the U87-MG cell line and the human brain cell line HEB to identify the transcriptional signatures of U87-MG cells and elucidate the role of hypoxia in the drug-resistant phenotype of GBM. Furthermore, we identified three key genes and explored their important roles in the drug resistance of hypoxic GBM.